Sodium–tin metal–organic framework anode material with advanced lithium storage properties for lithium-ion batteries - Wu, Na; Yang, Yu-Jing; Jia, Ting; Li, Tao-Hai; Li, Feng; Wang, Zhe (Journal of materials science, 2020)
Tin-based materials have a high theoretical capacity as a negative electrode material for lithium-ion batteries. However, the problem of volume expansion during lithium-ion insertion and extraction has severely limited its development. In this work, sodium–tin metal–organic framework (Na–Sn-MOF) compounds were successfully synthesized by simple reflux method. And we studied the reaction mechanism of the compound as anode materials for lithium-ion batteries. The special stable structure constructed by the 1,4-benzenedicarboxylic acid ligands and larger Na + ions will limit volume expansion of the tin effectively during the process of lithium–delithium. Therefore, the sodium–tin metal–organic framework anode material exhibits a high lithium storage capacity of 523 mAh g −1 with good cycling stability and rate capability. In addition, the Coulombic efficiency of the anode material for lithium-ion batteries is closed to 100% when the lithium ions are constantly embedded and released. This work for solving the problem of volume expansion of tin-based materials is quiet meaningful.